Chain makers in Cradley Heath, 1910 (1910)
1910 1880-1914 "Chain makers in Cradley Heath, 1910" [T0046.jpg], 1910 The Trade Boards Act 1909 introduced minimum wages in certain industries. In 1910, the Chainmaking Trade Board set a rate of 2½d per hour for adult women workers which was almost double the rate paid at the time. Mary Macarthur was one of the workers' representitives on the Trade Board. The employers at Cradley Heath in the West Midlands tried to delay the implementation of the new wage rate and in response the National Federation of Women Workers (NFWW) called a meeting in August 1910 at which the women refused to work at the old rates. The resulting strike attracted a great deal of public support and within a month 60% of employers had agreed to the rates. The remaining employers were boycotted until, 6 weeks later, they too agreed to pay. By 1911, the NFWW Cradley Heath Branch had 1700 members.